Exploring the knowledge and participation of university students on waste-to-wealth program in Surabaya - Siaputra, Hanjaya (School of Tourism, Universitas Ciputra Surabaya, 2024)
University activities have a significant impact on the environment. The sustainable development paradigm has emphasized the importance of sustainable waste management practices at all organizational levels, including the implementation of waste-to-value initiatives. This study was conducted to investigate the level of understanding and engagement of students regarding wasteful initiatives for asset improvement. Convenience sampling was used to collect data from 382 students at Petra Christian University (PCU), which were then analyzed using descriptive and inferential analysis. Results showed varying levels of understanding among students based on demographics and overall understanding of waste to asset initiatives was good (mean score = 4.21/6). However, the participation of most students in these initiatives is low (71.47%). This study shows that their knowledge and demographic background (year of study, education level, income) influence students' participation in waste to asset programs. These findings suggest that more efforts are needed to increase student participation in waste-to-wealth initiatives.